Parents’ views on sexual debut among pre-teen children in Washington, DC - Walker, Leslie R. (2008)
OBJECTIVE: Present US parents’ perceptions about factors leading to early intercourse and strategies for overcoming them. METHODS: Conducted analysis of eight focus groups with 78 male and female African-American and Hispanic caregivers of fifth-graders and sixth-graders (ages 10–12). RESULTS: Participants gave the following primary reasons for early sexual activity: lack of structured activities, adult supervision, and communication; and influence of peers, society, and media. They suggested strategies targeting these reasons, and the need for parents, schools, and the community to work together. CONCLUSION: Incorporating parents’ perspectives would help tailor interventions to the needs of the target population and increase parental support.